2019
DOI: 10.12691/jfnr-7-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index is Associated with Excessive Body Weight and Dietary Patterns in Subjects with Cardiometabolic Risk

Abstract: Unhealthy eating habits can trigger chronic inflammation in organs and tissues, and subsequent cardiovascular risk. Thus, this study aimed to evaluate the potential association of Dietary Inflammatory Index (DII™) score with cardiometabolic risk factors and a priori and a posteriori dietary patterns in adults and elderly Brazilians (42 ± 16 years) from a health care program. This cross-sectional study was carried out with 248 individuals (138 women and 110 men) from a Cardiovascular Health Care Program of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…Few previous studies were focused on the relationship between DII, HEI, and AHEI, which are in agreement with our results 27‐29 . A cross‐sectional study among 248 individuals aged greater than 20 years reported that DII was inversely associated with HEI 28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Few previous studies were focused on the relationship between DII, HEI, and AHEI, which are in agreement with our results 27‐29 . A cross‐sectional study among 248 individuals aged greater than 20 years reported that DII was inversely associated with HEI 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Few previous studies were focused on the relationship between DII, HEI, and AHEI, which are in agreement with our results 27‐29 . A cross‐sectional study among 248 individuals aged greater than 20 years reported that DII was inversely associated with HEI 28 . Inverse association between the most pro‐inflammatory diet (higher DII) and healthier diets by calculating HEI and AHEI was also found 27,29 .…”
Section: Discussionsupporting
confidence: 91%
“…Gibson-Smith et al showed that participants with depression/anxiety disorders consumed a poorer diet (with lower alternative healthy eating index [AHEI] and Mediterranean Diet Score [MDS]) in a 9-years follow-up cohort study [52]. HEI and AHEI reflect the diet quality and are associated with lower DII [53][54][55]. Philips et al showed a positive association between anxiety and DII (OR 1.60, 95% CI 1.15-2.24, p = 0.006) by comparing the highest and the lowest tertiles of DII [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, when a study aims to determine the average intake for a group or population, only a single R24h can be performed, especially when the sample size is large enough (75) . Additionally, this food survey has been used in epidemiological studies that evaluated the relation between food intake and cardiometabolic risk factors with promising results and acceptance by the scientific community (76)(77)(78)(79) . Finally, we did not measure serum histidine concentrations; however, plasma concentrations of amino acids may not directly reflect the consumption of these nutrients through the diet (20,80) .…”
Section: Discussionmentioning
confidence: 99%